Fetal Sex Chromosome Testing by Maternal Plasma DNA Sequencing: Clinical Laboratory Experience and Biology. Issue 2 (February 2015) - Bianchi, Diana W.; Parsa, Saba; Bhatt, Sucheta; Halks-Miller, Meredith; Kurtzman, Kathryn; Sehnert, Amy J.; Swanson, Amy
Abstract : OBJECTIVE: To describe the clinical experience with noninvasive prenatal testing for fetal sex chromosomes using sequencing of maternal plasma cell-free DNA in a commercial laboratory. METHODS: A noninvasive prenatal testing laboratory data set was examined for samples in which fetal sex chromosomes were reported. Available clinical outcomes were reviewed. RESULTS: Of 18, 161 samples with sex chromosome results, no sex chromosome aneuploidy was detected in 98.9% and the fetal sex was reported as XY (9, 236) or XX (8, 721). In 4 of 32 cases in which the fetal sex was reportedly discordant between noninvasive prenatal testing and karyotype or ultrasonogram, a potential biological reason for the discordance exists, including two cases of documented co-twin demise, one case of a maternal kidney transplant from a male donor, and one case of fetal ambiguous genitalia. In the remaining 204 samples (1.1%), one of four sex chromosome aneuploidies (monosomy X, XXX, XXY, or XYY) was detected. The frequency of false positive results for sex chromosome aneuploidies is a minimum of 0.26% and a maximum of 1.05%. All but one of the discordant sex chromosome aneuploidy results involved the X chromosome. In two putative false-positive XXX cases, maternal XXX was confirmed by karyotype. For the false-positive cases, mean maternal age was significantly higher in monosomy X ( P <.001) and lower in XXX ( P =.008). CONCLUSION: Noninvasive prenatal testing results for sex chromosome aneuploidy can be confounded by maternal or fetal biological phenomena. When a discordant noninvasive prenatal testing result is encountered, resolution requires additional maternal history, detailed fetal ultrasonography, and determination of fetal and possibly maternal karyotypes. LEVEL OF EVIDENCE: II Abstract : Noninvasive prenatal sex chromosome testing can be confounded by maternal or fetal phenomena; when results are discordant with ultrasonography or karyotype, consider alternative biological explanations.